Odpowiedzi

Najlepsza Odpowiedź!
  • Roma
  • Community Manager
2010-01-31T10:50:04+01:00
(-0,6a²b)² = dla a = -0,5 , b = 3⅓
= [-0,6 * (-0,5)² * 3⅓ ]² = (-⁶/₁₀ * (-½)² * ¹⁰/₃)² = (-⅗ * ¼ * ¹⁰/₃)² = (-½)² = ¼

(-1/x + x³)² * ⁸/₂₅ dla x = - ½
= [-1/- ½ + (- ½)³]² * ⁸/₂₅ = (2 - ⅛)² * ⁸/₂₅ = (1⅞)² * ⁸/₂₅ = (¹⁵/₈)² * ⁸/₂₅ = ²²⁵/₆₄ * ⁸/₂₅ = ⁹/₈ = 1⅛

√-4x³ + 12y - 5z dla x = -1 , y = ⅙ , z = -6
=√-4*(-1)³ + 12*(⅙) - 5*(-6) = √4 + 2 + 30 = √36 = 6
12 3 12
2010-01-31T10:53:37+01:00
(-0,6a²b)² dla a=-0,5 , b=3 całe i 1/3
[-0,6*(-0,5)² * (3 1/3)]²=
[-0,6 * 0,25 * 10/3]²=
[-6/10*25/100*10/3]²
[25/50]²=[1/2]²=1/4


(- 1/x + x³)² * 8/25 dla x= - 1/2
[-1/-1/2 + (-1/2)³]²=
[-1*(-2)+ (-1/8)]²=
[2-1/8]²=[16/8 -1/8]²=225/64


√-4x ³+12y-5z dla x=-1 , y= 1/6 , z=-6
√-4*(-1)³ + 12*1/6 - 5 *(-6)=
√-4*-1 + 2 +30=√4 +32=2+32=34
4 3 4
2010-01-31T10:53:57+01:00
(-0,6a²b)² dla a=-0,5 , b=3 całe i 1/3 wynosi zatem
[-0,6*(-0,5)²*3⅓]=[-0,6*0,25*10/3]=-½
(- 1/x + x³)² * 8/25 dla x= - 1/2 wynosi zatem
[-1/(-½)+(-½)³]²*8/25=(2-⅛)²*8/25=225/64*8/25=9/8=1⅛
√-4x³+12y-5z dla x=-1 , y= 1/6 , z=-6 wynosi zatem
√[-4*(-1)³+12*⅙-5*(-6)]=√(4+2+30)=√36=6
4 2 4